Influencing the extremes of growth : too tall - too small - Waal, Wouter de (Erasmus Universiteit Rotterdam, 1996)
The publication focuses on growth disorders in children, the role of growth hormone and the effects of GH treatment. Intended for professional public.
Keywords: Child; tělesná výška; pediatrie; Growth Hormone; poruchy růstu; Hormone Replacement Therapy; Growth Disorders; Body Height; hormonální substituční terapie; růstový hormon; genetika, lékařská genetika; dítě